Vessel Density in Glaucoma of Different Entities as Measured with Optical Coherence Tomography Angiography - Lommatzsch C; Rothaus K; Koch JM; Heinz C; Grisanti S (Clinical Ophthalmology, 2019)
C Lommatzsch,1 K Rothaus,1 JM Koch,1 C Heinz,1,2 S Grisanti3 1Department of Ophthalmology, St. Franziskus Hospital, Muenster 48145, Germany; 2Department of Ophthalmology, University of Essen, Essen, Germany; 3Department of Ophthalmology, University of Luebeck, Luebeck, GermanyCorrespondence: C LommatzschDepartment of Ophthalmology, St. Franziskus Hospital, Hohenzollernring 74, Muenster 48145, GermanyTel +49 2519352711Fax +49 2519352719Email claudia.lommatzsch@augen-franziskus.dePurpose: To compare papillary and macular vessel density (VD), as measured by optical coherence tomography angiography (OCTA), in eyes with primary open-angle glaucoma (POAG), normal-tension glaucoma (NTG) and exfoliation glaucoma (XFG).Methods: The papillary and macular VD of 40 eyes with POAG, 19 with NTG and 21 with XFG were examined using OCTA (AngioVue™). The VD was measured at two different layers of segmentation (optic nerve head: radial peripapillary capillary [RPC] and nerve head [NH]; macula: superficial [SL] and deep [DL] retinal vascular plexus) with a 4.5×4.5mm papillary and 6×6-mm macular scan. VD was calculated by an automated density measuring tool in the AngioVue™ software.Results: There were no significant differences in the total value of the papillary, peripapillary and macular VD. A significantly higher VD could be measured for NTG compared to POAG, as well as for XFG in the inferior nasal peripapillary sector at RPC-segmentation and at the NH-level between NDG and XFG.Conclusion: OCTA can detect a difference in VD in the nasal inferior peripapillary sector in NTG compared with POAG and XFG. These findings may help to improve the understanding of further pathophysiological mechanisms.Keywords: OCT angiography, glaucoma entities, blood flow, vessel density